EvapotranspiraÇÃo e coeficiente de cultivo para a beterraba sob estresse salino em ambiente protegido - Da Silva, Alexsandro Oliveira [UNESP]; Klar, AntôNio Evaldo [UNESP]; E Silva, ÊNio Farias de França; Cunha, E. Antonio Ribeiro [UNESP] (My University, 2014)
Crop evapotranspiration is the maximum loss of water that the crop undergoes in a particular stage of development when no water restriction occurs in the soil. In order to evaluate actual evapotranspiration of the beet crop, an experiment was conducted in a greenhouse at the Rural Engineering Department of the University of the State of São Paulo, College of Agricultural Sciences, Botucatu, SP, Brazil (22°57'34 S and 48º31'20 W) from April to June 2012. The effect of soil salinity with electrical conductivity values of 1.0; 3.0; 6.0; 9.0 and 12.0 dS m-1 in two beet cultivars (Early Wonder and Itapuã 202) were evaluated. The statistical design was randomized blocks with 40 plots. Actual maximum evapotranspiration of the crop was 101.8 and 89.5 mm. Values of Kc for the two cultivars showed mean decrease of 53% and 51.2% as compared with data from the literature. The increase in soil salinity led to a decrease in actual evapotranspiration of the Early Wonder cultivar, while an increase was observed in actual evapotranspiration of the Itapuã 202 cultivar up to the salinity threshold value of 6 dS m-1.
Evapotranspiration and crop coefficient (kc) for beet under salt stress
Keywords: Electrical conductivity; Irrigation management; Salinity